The Ethical Role of the Judge in the New Civil Code - Calixto, Rubens Alexandre Elias (2022)
The new Brazilian Civil Code brought forth important issues on procedures to be used in civil demands. Appeals were made extinct and procedural issues were added, coupled to modifications with regard to items in civil procedure. Besides procedure changes, the new CC presented a new feature for the judge, transforming him in a particular way in an administrator of the process in collaboration with the other partners. Several tools were produced never yet seen in the Brazilian CC. This made possible a greater flexibility of procedure and the personal intervention of the judge so that the procedure becomes more efficacious and more just in the issue. Several tools have been analyzed too. It is a great challenge for judges in their high mission through the effectiveness of the process and the constant insistence of the legal status.